PENGGUNAAN ASAP CAIR TANDAN KOSONG KELAPA SAWIT (TKKS) SEBAGAI PESTISIDA NABATI UNTUK MENGENDALIKAN HAMA PERUSAK DAUN TANAMAN SAWI (Brassica juncea L.) - Yulia P. Sari; Samharnto Samharinto; Bambang F. Langai (Universitas Lambung Mangkurat, 2018)
The aims of this research are to identify the dominant type of pest that attack mustard plants, to identify the component of liquid smoke of oil palm empty fruit bunches, to examine the effects of interaction between concentration level and frequency of application of liquid smoke spraying to the intensity of leaf damaging pests attack on mustard plants, to examine the effects of some concentration level and frequency of application of liquid smoke spraying severally to the intensity of leaf damaging pests attack on mustard plants, and to determine effective concentration and frequency of application of liquid smoke spraying to decrease the intensity of leaf damaging pests attack mustard plants. The research results showed that leaf damaging pests found have attacked mustard plants during the research period are Plutella xylostella L., Spodoptera litura, long caterpillar (Plusia spp.), and Crocidolomia binotalis. The test result for chemical content showed that liquid smoke of oil palm empty fruit bunches contained 20 types of chemical compounds. The compounds with the most content found are Ethylene glycol, Acetic Acid, Phenol/Benzenol & Benzene sulfonic acid/Carbamic acid, Acetone, and Butyrolactone with each successive concentration, i.e. 52,06 %, 22,67 %, 7,76 %, 4,67 %, and 2,77 %, where it is known that phenol and acetic acid are compounds that can play a role as insecticides for pests. The effect of treatments (liquid smoke concentration, spraying frequency, and their interaction) is very real different compared to without treatment spraying liquid smoke solution (control), while the effect of concentrations (2,5ml/l;5ml/l;7,5ml/l;10ml/l) of liquid smoke and spraying frequency (once, twice, and three times a week) and their interaction severally has no real effect, giving treatments (concentration and spraying frequency of liquid smoke) decrease the intensity of pests attack for 24,83%, increase the number of leaves for 8,36%, fresh weight of plants for 127,39%, and shoot-root ratio (SRR) for 44,62%.